2007
DOI: 10.1007/s00464-007-9362-1
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity for eye–hand coordination skill on a virtual reality laparoscopic surgical simulator

Abstract: Eye-hand coordination skill of the nondominant hand, but not the dominant hand, measured using the LAP Mentor was able to differentiate between subjects with different laparoscopic experience. This study also provides evidence of construct validity for eye-hand coordination skill on the LAP Mentor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 28 publications
(24 reference statements)
3
46
1
Order By: Relevance
“…EVA showed good construct validity both for 2D and 3D metrics. Time, path length, and depth are common parameters, which have been validated in many clinical studies [11,[44][45][46][47][48]. Average speed and acceleration are less widespread metrics, but also showed good discriminative scores [11,44,49].…”
Section: Discussionmentioning
confidence: 99%
“…EVA showed good construct validity both for 2D and 3D metrics. Time, path length, and depth are common parameters, which have been validated in many clinical studies [11,[44][45][46][47][48]. Average speed and acceleration are less widespread metrics, but also showed good discriminative scores [11,44,49].…”
Section: Discussionmentioning
confidence: 99%
“…Time to completion has been a popular parameter to evaluate surgical skills in arthroscopic and endoscopic training [2,8,12,15,18], although it cannot clarify the details of psychomotor skills in which the trainee lacks. These results of score and time data support the hypothesis that individuals with more experience in performing actual arthroscopic procedures also will perform better in simulated tasks.…”
Section: Discussionmentioning
confidence: 99%
“…However, depending on the nature and difficultness of the task, these metrics might not always show significant differences [57]. For these same tasks, a number of studies have shown that speed of movements can be a differentiating aspect [29,31,48]. This may partly be due to the difficulty of determining an optimal path, which in any case will depend on the task's goal.…”
Section: Clinical Definition Of Metricsmentioning
confidence: 99%